2014
DOI: 10.3109/01443615.2014.896882
|View full text |Cite
|
Sign up to set email alerts
|

Body weight, body image and primary postpartum haemorrhage: A review of the literature

Abstract: The prevalence of obesity during pregnancy is rising. Elevated BMI is a significant risk factor for adverse maternal and fetal outcomes, including primary postpartum haemorrhage (PPH). Addressing the issues surrounding obesity in pregnancy presents many biological, social and psychological challenges. BMI is an easily measured and modifiable anthropometrical risk factor and should be recorded in all pregnancies. BMI should be proactively managed prior to and during pregnancy. All women should be educated as to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…As a matter of fact, there is a notable lack of clarity in the association between BMI and PPH reported in observational studies. However, some studies [18][19][20] have suggested that maternal obesity is an important risk factor for PPH, while others [21][22][23] fail to find any effect of BMI on PPH. Several potential explanations can be offered for such conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, there is a notable lack of clarity in the association between BMI and PPH reported in observational studies. However, some studies [18][19][20] have suggested that maternal obesity is an important risk factor for PPH, while others [21][22][23] fail to find any effect of BMI on PPH. Several potential explanations can be offered for such conflicting results.…”
Section: Discussionmentioning
confidence: 99%